PENGARUH KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR IPA PESERTA DIDIK KELAS VIII SMPN 1 PALU SELAMA MASA PEMBELAJARAN DARING - Isnawati Nurdin (Program Studi Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Institut Agama Islam Negeri (IAIN) Palu, 2022)
This study aims to determine the effect of self-regulated learning on science learning outcomes for class VIII SMPN 1 Palu students during the online learning period. This study is a quantitative study using a cross-sectional survey design. The sample in this study amounted to 181 class VIII students of SMP Negeri 1 Palu in the 2020/2021 school year. Data collection was carried out using instruments in a self-regulated learning scale questionnaire and student learning outcomes tests. The data analysis technique used in this study was regression analysis. The results showed that there was a significant influence of self-regulated learning on the science learning outcomes of class VIII SMPN 1 Palu students during the online learning period